Crossroads of vibrational (infrared and Raman) spectroscopy and X-ray powder diffraction in identification and characterization of some minerals – advantages and limitations. A review - Makreski, Petre; Pejov, Ljupco; Jovanovski, Gligor (Society of Chemists and Technologists of Macedonia, 2024)
Many analytical methods have been successfully employed for the study of minerals, in particular, vibrational infrared (FTIR) and Raman spectroscopies and X-ray powder diffraction (XRPD). The advantages of the vibrational spectroscopic techniques for identifying and characterizing minerals include: rapid and versatile use; qualitative and quantitative chemical signatures; distinctive chemical fingerprint of a material; indirect determination of the crystal features (polymorphism, isomorphism, coordination, degree of deformation of structural polyhedra); small sample quantity (area less than 1 μm2 for Raman); wide coverage of 4,000 – 50 cm−1 region in a single scan; in situ and direct measurements without sample preparation; nondestructive use; etc. On the other hand, XRPD is a destructive technique that, depending on the method used and the density of the material, requires from a few micrograms up to around 5 grams of sample quantity for analysis. In spite of that, it is a rapid and powerful technique used in mineral studies with relatively straightforward interpretation of the results. During the last decade, portable X-ray powder diffractometers for the nondestructive analysis of art and archeological materials have been developed along with the portable and hand-held vibrational spectroscopy instrument. Here, some advantages and limitations in the process of the complementary use of FTIR and Raman vibrational spectroscopy and XRPD for identification and characterization of minerals are outlined.